The body unbound: philosophical perspectives on politics, embodiment and religion - Mjaaland, Marius Timmann; Sigurdson, Ola; Sigridur Thorgeirsdottir (Cambridge Scholars, 2010)
A philosophical inquiry into politics, embodiment and religion takes us straight to some of contemporary culture's most notorious issues: suicide bombing, the veiled and the exposed body, and present-day biopolitics. Interpretations of the body have alway